A comparison of the prokaryotic communities associated with seven seaweed species, sediment, and seawater from the Penghu archipelago, Taiwan. Issue 10 (25th November 2020) - Cleary, Daniel F. R.; Huang, Yusheng M.
ABSTRACT: Seaweeds are a diverse, abundant, and ecologically important component of coral reef ecosystems. However, relatively little is known about their prokaryotic communities. In the present study, we assessed the prokaryotic communities of seven seaweed species, sediment, and seawater sampled in seas of the Taiwanese Penghu archipelago. The most abundant phyla in terms of sequences and OTUs were Proteobacteria, Bacteroidetes, Tenericutes, Actinobacteria, Planctomycetes, Cyanobacteria, and Verrucomicrobia. This fits well with previous seaweed studies with the notable exception of Tenericutes. Tenericutes members were only abundant in the species Halimeda opuntia and Sargassum hemiphyllum var. chinense . One OTU, assigned to the genus Mycoplasma, dominated all samples of H. opuntia . The main difference in prokaryotic composition was between samples of the green seaweed H. opuntia and samples of the green seaweed species Caulerpa racemosa and Chlorodesmis fastigiata . The predicted functional profile of C. fastigiata was also distinct from that of the other seaweed species. There was also clear compositional variation between green and brown seaweed species with Verrucomicrobia abundance higher in brown seaweed species. OTU richness was also higher in brown than green seaweed species. The prokaryotic communities found in all seaweed species were compositionally distinct from those found in sediment and seawater. Most of the abundant OTUs sampled in the present study had high sequence similarities to organisms obtained from a range of hosts including sponges, corals, and other seaweed species.